The Application of Mamdani Method for Predicting The Best Portable Computer Based on Hardware and Price - Gelar Lailatul Qodar (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2020)
A portable computer is a technology tool widely used among students and students. With a very helpful role as in typing needs, presentations, and math calculations. A variety of carry-on computers that many certainly make one difficult to determine a decent and good portable computer to use. In general, in the process of selecting a portable computer, there is no recognized standard to determine the recommended portable computer level. The purpose in this research is to produce predictive values that will be a reference in supporting decisions in determining a portable computer that complies with hardware component criteria and pricing. This study implemented FIS Mamdani models with the analysis stage of the formation of fuzzy sets, application of implications function, rule composition and defuzification. The result of this research is an output of predictive value based on hardware component inputs and prices that will assist the user in supporting decisions in determining the best carry-on computer and according to what they want.Keywords: Predictions, Fuzzy Inference System, Mamdani methods, portable computers, students.